Do Users Always Trust More when Blog Posts are Related to the Blog’s Theme?: The Degree of Relevance and Its Effect on Message Credibility - 김지열; 이철 (경영정보학연구, 2018)
When people try to find restaurant information via search engine results, they look at posts not only from sites with solely restaurant reviews but also from sites with restaurant unrelated contents. This study aims to investigate whether relevance between post and blog type affects users’ trust toward a review. This study also attempts to check if the above effects interact with age. We designed a restaurant review post for two different blogs: one featuring restaurant review and another that does not feature restaurant reviews. After our participants visited one restaurant review post, they answered our questionnaire. We conducted an online survey on 206 participants to test our research model. Results show that 1) the effect of relevance between post and blog type on message credibility, which is users’ trust toward restaurant reviews, is not greater when posts are consistent with the theme of a blog. 2) Among users who are over 30 years old, relevance between post and blog type moderates the relationship between media skepticism, which is users’ feeling of mistrust toward blog, and belief in expertise, that is, users’ belief that the review post provides sufficient restaurant information. 3) Users’ perceived value of the restaurant review post mediates the relationship between users’ belief in the expertise in a post and users’ intention to seek additional information.
Keywords: 블로그; 신뢰; 매체 의구심; 전문성; 지각된 가치; 추가적인 정보 검색 의도; 맛집 리뷰; Blog; Users’ Trust; Media Skepticism; Expertise Belief; Perceived Value; Intention to Seek Additional Information; Relevance; Restaurant Review